(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We present a short history of the following problem: Classify the finite groups G, so that the group of units of the integral group ring Z G contains a subgroup of finite index isomorphic to a direct product of nonabelian free groups.